Constructing Cu7S4@SiO2/DOX Multifunctional Nanoplatforms for Synergistic Photothermal–Chemotherapy on Melanoma Tumors - Zhang, Leilei; Pan, Hui; Li, Yongyun; Li, Fang; Huang, Xiaolin (Frontiers in Bioengineering and Biotechnology, 2020)
The integration of photothermal therapy and chemotherapy has been recognized to be an efficient strategy through the instant thermally ablation and long-term chemical inhibition, thus achieving high therapeutical effect. In the present work, we designed and prepared Cu7S4@SiO2/DOX nanocomposites and used them as efficient nanoplatforms for synergistic photothermal-chemo therapy on melanoma tumors. The Cu7S4@SiO2/DOX was constructed by firstly synthesizing Cu7S4 nanocrystals, then in-situ growing SiO2 shell on the surface of Cu7S4 nanocrystals, and finally loading DOX within SiO2 shell. The Cu7S4@SiO2/DOX was composed of Cu7S4 core as the photothermal transducer, SiO2 shell as DOX carrier and DOX as the model of anticancer drug. Once exposed to a 1064 nm laser, the Cu7S4@SiO2/DOX could simultaneous generate heat for photothermal therapy and accelerate the DOX release. When the Cu7S4@SiO2/DOX was injected into the center of tumor, the tumor exhibit rapid temperature elevation once exposed to the NIR laser and the tumor growth is significantly inhibited through the synergistic photothermal-chemo therapy, in comparison to the limited therapeutical effect of photothermal therapy or chemotherapy alone. Therefore, the Cu7S4@SiO2/DOX with photothermal-chemo function can be used as excellent nanoplatforms for treating solid tumor with high theoretical effect.